Developing an indicator of poverty liableness through an analysis of household risk management strategies: a case towards the development of a formal social protection scheme in Malaysia - Abdul Jalil, Ahmad Zafarullah; Harun, Mukaramah; Che Mat, Siti Hadijah; Majid, Rahimah; Samsudin, Shamzaeffa (Universiti Utara Malaysia, 2013)
Malaysia has been recognized as one of the countries that has successfully reduced the problem of poverty among its population. In 1970, the poverty level stood at 49.3 percent of the total population. The rate was later reduced to 8.1 percent in 1999 before reaching 3.7 percent in 2011 (Department of Statistics Malaysia, 2011). However, the recent trend in the literature that moved towards the reconceptualisation of poverty in terms of insecurity or vulnerability, have brought out another issue of how poverty should be tackled in Malaysia.In this study, we examined how rural households in Malaysia behaved when faced with a risk and how this would affect their livelihood and therefore the level of vulnerability to poverty.For this purpose, we have conducted a survey on 499 rural households across all the states in Peninsular Malaysia. Our findings show that rural households in Malaysia faced a variety of risks and they have employed several strategies in order to cope with the risks. However, not all these strategies are effective in dealing with the risk and this has resulted in a negative impact on the livelihood of the households.Our study also found that income and savings level are the main factors that will determine the odds for a household to recover from a crisis.The findings of this study imply that there is room for the government or any other relevant authorities to intervene to improve the availability and effectiveness of risk coping strategies of rural households in Malaysia.